Beta blockers: an overview on the current established therapeutic uses on different classes of patients for a deeper understanding on the proper utilization while prescribing a drug - Naveed, Ahmed Issa Jahangir (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.